Rab GTPase Mediating Regulation of NALP3 in Colorectal Cancer - Gülçin Tezcan; Ekaterina E. Garanina; Margarita N. Zhuravleva; Shaimaa Hamza; Albert A. Rizvanov; Svetlana F. Khaiboullina (Molecules, 2020)
The NALP3 inflammasome signaling contributes to inflammation within tumor tissues. This inflammation may be promoted by the vesicle trafficking of inflammasome components and cytokines. Rab5, Rab7 and Rab11 regulate vesicle trafficking. However, the role of these proteins in the regulation of inflammasomes remains largely unknown. To elucidate the role of these Rab proteins in inflammasome regulation, HCT-116, a colorectal cancer (CRC) cell line expressing pDsRed-Rab5 wild type (WT), pDsRed-Rab5 dominant-negative (DN), pDsRed-Rab7 WT, pDsRed-Rab7 DN, pDsRed-Rab11 WT and pDsRed-Rab11 DN were treated with lipopolysaccharide (LPS)/nigericin. Inflammasome activation was analyzed by measuring the mRNA expression of NLRP3, Pro-CASP1, RAB39A and Pro-IL-1β, conducting immunofluorescence imaging and western blotting of caspase-1 and analysing the secretion levels of IL-1β using enzyme-linked immunosorbent assay (ELISA). The effects of Rabs on cytokine release were evaluated using MILLIPLEX MAP Human Cytokine/Chemokine Magnetic Bead Panel-Premixed 41 Plex. The findings showed that LPS/nigericin-treated cells expressing Rab5-WT indicated increased NALP3 expression and secretion of the IL-1β as compared to Rab5-DN cells. Caspase-1 was localized in the nucleus and cytosol of Rab5-WT cells but was localized in the cytosol in Rab5-DN cells. There were no any effects of Rab7 and Rab11 expression on the regulation of inflammasomes. Our results suggest that Rab5 may be a potential target for the regulation of NALP3 in the treatment of the CRC inflammation.